Mossbauer study of iron-containing carbon nanotubes - Marco, J; Gancedo, JR; Hernando, A; Crespo, P; Prados, C; Gonzalez, J; Grobert, N; Terrones, M; Walton, D; Kroto, H (2002)
Fe-57 transmission Mossbauer at temperatures between 18 and 298 K and magnetic measurements have been used to characterize Fe-filled carbon nanotubes which were prepared by pyrolisis of Ferrocene + C-60 at atmospheric pressure under an Ar atmosphere at 1050 degreesC. The Mossbauer data have shown that the Fe phases encapsulated within the carbon nanotubes are alpha-Fe, Fe3C and gamma-Fe. The magnetic results are compatible with the Mossbauer data. Taken together the results allow us to propose a simple picture of the distribution of iron phases within the carbon nanotubes which would consist of an alpha-Fe core surrounded by an gamma-Fe shell, finally covered by an Fe3C layer.